Study of Clinical outcome of Proximal Interphalangeal Joint Fractures Treated with Suzuki Frame - Pratyay Mukherjee; Arijit Saha; Debajyoti Sarkar (Asian Journal of Medical Research, 2021)
Background: Proximal interphalangeal (PIP) joint injuries are very common and occur frequently after a direct axial trauma to extended finger. Different modalities of treatments are available in this type of injury such as extension block splinting, the Hynes and Giddings device, ORIF with interfragmentary screw and many others. In present study Suzuki frame has been chosen for treatment of such fractures proposed by Suzuki et al in 1994. The aims & objectives is to describe the clinical outcome of treatment of proximal interphalangeal (PIP) joint fractures by dynamic Kirschner wire fixator in the form of Suzuki Frame. Subjects and Methods: We reviewed our 16 consecutive cases of PIPJ fractures treated with Suzuki frame. Regular clinical and radiological evaluation was done at 2 weeks, 4 weeks, 6 week and 12 weeks follow up. Visual Analogue Score(VAS), Range of motion of the PIPJ, Average Michigan hand Score were calculated and complications if any were noted. Result: Average Michigan hand questionnaire was 86.31% (range from 71%-94%). The average PIP ROM 96.25?  (Range 70?-120?). VAS Score improved  from average pre-op 8.25 to 0.5 in post-operative period. No angular deformity or instability noted at the end of follow up. Pin tract infection reported in two patients. Conclusion: The Suzuki Frame is easy to apply, safe, soft tissue sparing, minimally invasive technique. It can reduce and maintain reduction of unstable proximal interphalangeal joint fractures and allow immediate post-operative PIP joint motion with minimal complications.